Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Pemoderasi Pada Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018 - Meze, Maria Florentina; Tohari, Amin (Universitas Nusantara PGRI Kediri, 2020)
The value of the company is one of the measuring tools for profit because it will bring success to leaders and managers in managing company finances. Shareholders want high company value. High company value reflects high share value, so that it is considered to provide high welfare to shareholders. Bargaining for financial contracts in a company requires company size. The purpose of this study was to examine the effect of Profitability (ROA), Leverage (DER) and the disclosure of Corporate Social Responsibility on firm value with firm size as a moderating variable. The population in this study is mining companies listed on the Indonesian stock exchange for the 2016 - 2018 period. The sample used is 20 companies. The method used in this research is multiple linear regression method using the ex post facto quantitative approach. Hypothesis testing uses the t test. The results show (1) Profitability (ROA), Leverage (DER) and Corporate Social Responsibility have a significant effect on firm value, while Leverage (DER) and Corporate Social Responsibility partially do not have a significant effect on firm value. (2) Company size is able to moderate Profitability (ROA), Leverage (DER) and Corporate Social Responsibility (CSR).